Comparing Urban Qualities: A City Livability Framework Applied to Jakarta and Nusantara Capital City - Pandu K. Utomo; Anisah Azizah; Putri Nopianti; Nur Asriatul Kholifah; Kartika Tristanto; Ratri Bodromulatsih (Malikussaleh University, Aceh, Indonesia, 2026)
This research develops a systemic framework for analyzing urban livability by applying the DPSIR (Drivers, Pressures, States, Impacts, Responses) model to the contrasting cases of Jakarta, Indonesia's established megacity, and Nusantara Capital City (IKN), the planned new capital. Through a systematic literature review and comparative case analysis, we move beyond static indicators to reveal the dynamic causal mechanisms shaping livability. The findings indicate that Jakarta's unmanaged organic growth has established a negative feedback loop of uncontrolled urban intensity, resulting in three interrelated consequences: significant environmental deterioration, substantial economic losses from persistent congestion, and compromised resident well-being. In contrast, IKN's